2016
DOI: 10.2967/jnumed.115.169755
|View full text |Cite
|
Sign up to set email alerts
|

11C- or 18F-Choline PET/CT for Imaging Evaluation of Biochemical Recurrence of Prostate Cancer

Abstract: Recurrence of prostate cancer is suspected when an increase in the prostate-specific antigen level is detected after radical treatment; the recurrence could be local relapse, distant relapse, or both. Differentiation between the two patterns of relapse is critical for choosing the proper treatment strategy. Choline PET/CT could be of help in discriminating patients with local, lymph node, and bone recurrences, thus having an impact on patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Patients with positive MRI and PET/CT findings had PSA values that were significantly greater than those observed in patients with negative findings on the imaging tests. In fact, although we only found an association between PSA values at the time of biochemical failure and MRI positivity, many studies have reported an association between PSA and choline PET/CT [22]. Thus, after RP, the optimal PSA cut-off level for choline PET/CT analysis seems to be between 1 and 2 ng/mL [23], while for MRI, the corresponding value appears to range from 0.3 to 0.54 ng/mL [5].…”
Section: Discussionmentioning
confidence: 53%
“…Patients with positive MRI and PET/CT findings had PSA values that were significantly greater than those observed in patients with negative findings on the imaging tests. In fact, although we only found an association between PSA values at the time of biochemical failure and MRI positivity, many studies have reported an association between PSA and choline PET/CT [22]. Thus, after RP, the optimal PSA cut-off level for choline PET/CT analysis seems to be between 1 and 2 ng/mL [23], while for MRI, the corresponding value appears to range from 0.3 to 0.54 ng/mL [5].…”
Section: Discussionmentioning
confidence: 53%
“…The most widely used PET tracer for diagnosing PCa is 11 C-choline 6. 11 C-Choline-PET has been used for detecting osteolytic and osteoblastic metastatic lesions in patients with PCa 6; however, Nanni et al 36 recently reported that the T/BG ratios of 18 F-fluciclovine were greater than 11 C-choline in PCa relapse including bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…11 C-Choline-PET has been used for detecting osteolytic and osteoblastic metastatic lesions in patients with PCa 6; however, Nanni et al 36 recently reported that the T/BG ratios of 18 F-fluciclovine were greater than 11 C-choline in PCa relapse including bone metastasis. We also showed that 14 C-fluciclovine was superior to 3 H-choline for detecting lesions in osteoblastic metastasis model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, positron emission tomography-computed tomography (PET-CT), with tracers such as 18 F-choline, has increasingly played a role in the management of these patients [5,6]. However, sensitivity is only moderate for This article is part of the Topical Collection on Oncology -Genitourinary * Meghana Kulkarni Mkulkarni1@gmail.com detecting nodal metastases [5] or in those with low PSA levels at biochemical recurrence (BCR) [7]. This has led to the investigation of more prostate-specific tracers with greater diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%